The comparative value of shelled corn and hybrid grain sorhum prepared for feeding by different milling processes. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
Grain sorghums are being grown extensively in many parts of Kansas. Feeding tests with swine at this station have given excellent results when sorghum grain was compared with corn. Hybrid sorghum grains also have done well in the feedlot. Mills and elevators now can process grains in ways not previously possible. Interest in the new processes is increasing because they may improve the efficiency of the grains for feeding and thus provide more profit in hog raising. Five lots of pigs were self-fed free choice in drylot. All lots received a mixed animal and plant protein supplement of 4 parts tankage, 4 parts soybean meal, 1 part cottonseed meal, and 1 part alfalfa meal. The ration for each lot varied in the following manner:
Keywords: Swine; Shelled corn; Grain sorghum; Milling